Newborn Screening for Methylmalonic Acidemia in a Chinese Population: Molecular Genetic Confirmation and Genotype Phenotype Correlations - Zhou, Wei; Li, Huizhong; Wang, Chuanxia; Wang, Xiuli; Gu, Maosheng (Frontiers in Genetics, 2019)
Background: Methylmalonic acidemia (MMA) incidence was evaluated based on newborn screening in Xuzhou from November 2015 to December 2017, the clinical, biochemical and molecular characteristics of patients with MMA harboring MMACHC and MUT mutations were summarized. Methods: During the study, 236,368 newborns were screened for MMA by tandem mass spectrometry (MS/MS) in the Maternity and Child Health Care Hospital of Xuzhou. C3, C3/C2 and methionine, and tHcy if necessary, were measured during the first screening. Blood samples from the infants and/or their family members were used for DNA analysis. The entire coding regions of the MMACHC and MUT genes associated with MMA were sequenced by DNA MassARRAY and next-generation sequencing (NGS). Results: Eleven patients with MMACHC mutations and three with MUT mutations were identified among the 236,368 screened newborns; the estimated total incidence of MMA was 1:16,883. Among the MMA patients, two died of infection-triggered metabolic crisis approximately 3 months after birth. All the patients identified had two mutant alleles except for one individual with early-onset disease. The most common MMACHC mutation was c.609G>A. The laboratory levels of C3 and C3/C2 were elevated in MMA individuals compared to other infants. Importantly, we demonstrate that accelerated C2 degradation is related to air temperature and humidity. Conclusion: Our study reports the clinical characteristics of MMA and diagnosis through MS/MS and NGS. There was a higher incidence of MMA with homocysteinemia than of isolated MMA in Xuzhou. Insight from this study may help explain the high false-positive rate of MMA in summer.